Description of the final stadium larva of Erythrodiplax bromeliicola Westfall 2000 (Odonata: Libellulidae) with notes on variation in adults from Cuba - Trapero-Quintana, Adrian; Novelo-Gutiérrez, Rodolfo (Zootaxa, 2012)
The final stadium larva of Erythrodiplax bromeliicola Westfall is formally described and illustrated. The light brown scape and pedicel and creamy pale flagellum of the antenna, plus the abundant short, reddish, spiniform setae on the integument of the body surface and epiproct, comprise an exclusive combination of characters in the larva of E. bromeliicola. Information on larval habitat and a key for the larvae of the five Erythrodiplax species occurring in Cuba are provided. Details on morphological variation of an adult population from Cuba are also provided.